T-cell alpha beta + and gamma delta + deficient mice display abnormal but distinct phenotypes toward a natural, widespread infection of the intestinal epithelium. - Roberts, S J (1996)
Vertebrate immune systems contain T cells bearing either alpha beta or gamma delta T-cell antigen receptors (TCRs). alpha beta T cells perform all well-characterized T-cell effector functions, while the biological functions of gamma delta + cells remain unclear. Of particular interest is the role of gamma delta + cells during epithelial infections, since gamma delta + cells are commonly abundant within epithelia. Eimeria spp. are intracellular protozoa that infect epithelia of most vertebrates, causing coccidiosis. This study shows that in response to Eimeria vermiformis, mice lacking alpha beta T cells display defects in protective immunity, while mice lacking gamma delta + cells display exaggerated intestinal damage, apparently due to a failure to regulate the consequences of the alpha beta T cell response. An immuno-downregulatory role during infection, and during autoimmune disease, may be a general one for gamma delta + cells.